Use of zirconium-phosphate-carbonate chemistry to immobilize polycyclic aromatic hydrocarbons on boron-doped diamond - Mazur, Maciej (Langmuir : the ACS journal of surfaces and colloids, 2005)
We report on the formation of monomolecular layers of perylene- and pyrene-alkanoic acids on boron-doped diamond (BDD) substrates. The carboxylic acid layers are bound by coordination to zirconium phosphate (ZP) functionalities on the BDD substrate surface. The resulting Zr-phosphate-carbonate (ZPC) linkages between the substrate and the adlayer are asymmetric, of the form -(OPO3(2-) Zr4+-O2C-R)+ X-. Pyrene and perylene are well-established optical probes of polarity and viscosity at interfaces. We have used electrochemical and steady-state fluorescence techniques to study the loading density and behavior of these monomolecular films, allowing comparison of BDD and indium-doped tin oxide (ITO) substrates. Electrochemical data suggest that the pyrene chromophores are positioned roughly at the same distance from the surface, regardless of the length of the anchoring alkanoic acid chain, a finding that can be explained by the pyrene lying on the substrate surface. Such a conformation is plausible given the surface coverage (5 x 10(-11) mol/cm2, ca. 0.1 monolayer) we measure for these systems